Renal Dose Adjustment Management for Herpes Zoster in Immunocompromised Patient with Renal Impairment: A Case Report and Literature Review - Hapsari Kinanti; Hasnikmah Mappamasing; Trisiswati Indranarum; Medhi Denisa Alinda; Linda Astari; Afif Nurul Hidayati (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2025)
Background: Herpes zoster is a reactivation of varicella-zoster virus that is characterized by a painful dermatomal vesicle eruption. Herpes zoster can bring several burdens including a painful rash and complications such as herpetic neuralgia and other neurological disorder. Herpes zoster commonly affects persons with decreased immunity levels which can caused by several conditions including malignancy. Multiple myeloma is one of the haematological malignancies commonly associated with renal impairments. Acyclovir is excreted in an unchanged form through renal, thus in patients with renal impairment could decrease the excretion level and can increase the possibility of renal toxicity. Case Presentation: We present a case report of a 46-year-old herpes zoster patient with multiple myeloma and renal impairment. The renal dose adjustment for acyclovir was done in this patient becomes 800mg three times daily. One week after the administration of acyclovir this patient showed remarkable results, there was no new lesion was found. This patient resolved after 10 days of renal dose adjustment of oral acyclovir and continued the multiple myeloma treatment on day fourteen. Conclusion: The management of herpes zoster infection in a patient with multiple myeloma commonly accompanies with renal impairment thus the consideration of adjusting the dose for renal impaired condition is important to reduce the possibility of renal toxicity in concordance with maintaining its adequate dose to prevent the possibility of complication